2020
DOI: 10.1080/15438627.2020.1716228
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the determinants of success in different clusters of ball possession sequences in soccer

Abstract: The purpose of this study was two-step: classify ball possession (BP) according to the duration and number of passes; identify which tactical variables most discriminate the different BP. We obtained 527 BPs from four official matches of the Brazilian Soccer Championship 2016. Forty-one 'notational', 'space occupation', and 'displacement synchronization' predictor variables were used.The BPs were classified into three groups: short (11.07 ± 4.49s, 1.93 ± 0.99 passes), medium (26.83 ± 7.33s, 5.41 ± 1.84 passes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 35 publications
0
32
1
4
Order By: Relevance
“…One of the most important and most studied performance indicators in the scientific literature in male soccer has been ball possession [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Analyzing all these studies and their relationship with possession shows that there is not yet a scientific consensus that allows to establish robust recommendations for men’s football teams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important and most studied performance indicators in the scientific literature in male soccer has been ball possession [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Analyzing all these studies and their relationship with possession shows that there is not yet a scientific consensus that allows to establish robust recommendations for men’s football teams.…”
Section: Introductionmentioning
confidence: 99%
“…We still do not have conclusive data on whether possession is necessary to achieve victory, or something not related to success. Currently, ball possession is considered a complex phenomenon [ 26 ], and for this reason there is still more literature needed in this field. There are many variables that have been related to this performance indicator, from the many championships that have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The positive influence of the complex methodology for the development of physical qualities and accuracy of strikes among young football players is also shown in studies [4,5,6]. Peker, Böge, Bailey, Wagman, Stoffregen [4] showed that with an increase in the level of preparedness, the strength and accuracy of strikes in football increase.…”
Section: Introductionmentioning
confidence: 79%
“…To determine the performance of structured training, identify relationships between indicators of physiological function and performance of physical and technical preparedness correlation analysis was conducted performance testing of athletes control Health, sport, rehabilitation Здоров'я, спорт, реабілітація Здоровье, спорт, реабилитация 7(1) and experimental groups before and after the experiment (Table. [5][6][7][8]. Prior to the experiment, the number of reliable relationships between psychophysiological indicators and indicators of physical and technical preparedness in both the control and experimental groups was 5-6 interconnections (Table 5, 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation